Drug, demon, or donut? Theorizing the relationship between social media use, digital well-being and digital disconnection - Halfmann, Annabell (2022)
Social media overuse is a central concern in discussions over digital well-being. Digital disconnection is often presented as a solution to this problem, but mixed evidence on its effectiveness suggests we lack understanding of why, how and when disconnection works. Drawing from three recurrent social media metaphors - the drug, demon and donut metaphor - this article aims to advance understanding of social media disconnection by developing a classification of disconnective mechanisms in accordance with three conceptual approaches to social media overuse. This classification provides theory-driven support for differing social media disconnection mechanisms. We discuss its implications for practice and future research.